Regulatory Harmonisation - Issues for New Zealand - Kevin Guerin (New Zealand Government, The Treasury, 2001)
This paper discusses aspects of harmonisation of regulatory structures (occupational, product approval etc) between jurisdictions. The primary focus is on trans-national arrangements, but many of the issues also apply to relations between central and regional/local government, and between regional/local governments. The paper addresses a taxonomy of harmonisation approaches, who to harmonise with, how far and in what areas, and a range of implementation issues, before reviewing some relevant EU examples, outlining existing trans-Tasman regulatory relationships and current trans-Tasman harmonisation proposals, and noting some issues relevant to local government. It does not address wider economic integration issues or currency or political union.
Keywords: 330